FARMERS’ PREFERENCES FOR GOAT BREEDS IN PUNJAB, PAKISTAN - M. S. Muhammad; M. Abdullah; M. S. Khan; K. Javed; M. A. Jabbar (Journal of Animal and Plant Sciences, 2015)
Goat keepers prefer some breeds on the others due to their indigenous knowledge about breeds. The aim of present study was to gather firsthand knowledge about farmers’ preferences for certain goat breeds by using household survey technique. Six villages at two diverse sites were randomly selected and 55 households keeping goats were interviewed in each village in the Punjab province of Pakistan. Stratified random sampling was conducted by stratification of houses based on ownership of goats. Distribution of breeds showed highest average number of Beetal brown (8.12±9.13) and crossbred goats (5.50±2.12) at sites I and II, respectively. Among does, Beetal×Teddy cross and Beetal black had the highest number at sites I and II, respectively. Percentages of farmers who preferred Beetal brown-splashed for maturity, conception rate and number of kids at Site I were 33.3, 45.4 and 41.9%, respectively and 25.6%, 31.9% and 25.3% farmers chose Beetal Black for these traits at Site-II, respectively. Birth weight, twinning percentage, preweaning survival rate were preferred for Beetal brown splashed by 46%, 46.9% and 52.2% farmers at Site-I and Beetal black by 22.9%, 31.9% and 31.5% farmers for the same traits at Site-II, respectively. Farmers showed preference for Beetal brown-splashed for growth rate (45.0%), dressing percentage (49%) and meat quality (46%) at Site-I and Beetal black was preferred for the same traits by 33.5%, 24.5% and 30.8% farmers at Site-II, respectively. For high milk yield and milk quality 34.5% and 29.2% farmers preferred Beetal brown-splashed at Site-I, while 24.4% and 7.14% farmers preferred Beetal black for these traits at Site-II, respectively. 46.7%, 45.8% and 43.4% farmers preferred Beetal brown-splashed for survival rate, resistance to parasites and disease resistance at Site-I while 26.6%, 26.5% and 24.7% farmers preferred for Beetal black for these traits at Site-II, respectively. Nice physical appearance, skin colour and large body size were preferred traits for Beetal brown-splashed by 41.3%, 43% and 56% farmers at Site-I and for Beetal black 24%, 36% and 31% farmers at Site-II, respectively. It was suggested that more emphasis should be given for the improvement of rural goat flocks considering preferred traits and flock size should be increased to provide more financial benefits to the rural farmers.
Keywords: goat performance and conformation; household survey; farmers’ choice; goat breeds